The Influence of Trust, Service Features, and Product Knowledge on DANA E-Wallet User Satisfaction Among Digital Business Students at UNIMED - Nerva, Souza Al-Gibrani; Aprinawati, Aprinawati (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
This study aims to examine the influence of trust, service features, and product knowledge on user satisfaction with the Dana e-wallet application among students of the Digital Business Study Program, Faculty of Economics, Universitas Negeri Medan. A descriptive quantitative approach was employed, using purposive sampling to select 73 respondents who had used the Dana application for at least six months. Data were analyzed using multiple linear regression to assess both simultaneous and partial effects of the independent variables on user satisfaction. The results show that trust and product knowledge have a positive and significant effect on user satisfaction, while service features do not have a significant influence. The coefficient of determination (R²) is 0.731, indicating that 73.1% of the variation in user satisfaction can be explained by the three independent variables, while the remaining 26.9% is influenced by other unexamined factors. These findings highlight the importance of building user trust and enhancing product understanding as key strategies for improving satisfaction with the Dana e-wallet.